Pengaruh Lingkungan Kerja Fisik Dan Iklim Organisasi Terhadap Semangat Kerja Pegawai: (Studi Kasus Pada Kantor Desa di Kecamatan Rajapolah Kabupaten Tasikmalaya) - Sigit Pratama; Rita Tri Yusnita; Nita Fauziah Oktaviani (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
This study aims to determine the effect of the physical work environment and organizational climate on morale ( a case study of village office employees in Rajapolah sub-district). The method used in this study is causality through a survey approach, with the sample to be selected in this study being Village Office employees in Rajapolah District, namely 49 respondents. The analytical tool used in this study was multiple regression using SPSS version 25. The results showed that the Physical Work Environment and Organizational Climate had a significant influence on the Morale of Village office employees in Rajapolah district. Organizational climate has a significant influence on the morale of Village Office employees in Rajapolah District.